Studi Komposit Potensi Jagung pada Lahan Sawah Tadah Hujan Setelah Pertanaman Padi - Misran, Misran (Politeknik Negeri Lampung., 2013)
Studies on the potential of composite maize rainfed lowland after rice. Assessments conducted in rainfed lands who have had more than 3 years fallow in Kenagarian Surantih South Coastal District of West Sumatra Province, in MK 2010. The area of 4 hectares, using the 2 new improved maize composite VUB (Sukmaraga and Bisma) with system WCS (Without Cultivating the Soil), spacing of 80 x 40 cm, VUB each planted 2 seeds / hole. Fertilizers used 200 kg of Urea, 100 kg SP-36, 100 kg KCl, 500 kg Dolomit, and 2 ton/ha dung . Data were collected for plant height, yield components, and results, and analysis of farming. With corn Bisma VUB WCS system can provide results 6.84 t/ha with a gain of Rp 7.670.500,-VUB Sukmaraga while corn yield 6.65 t/ha with profit Rp 7.347.500,- Keywords: Corn, VUB, production, potential